Abnormalities of Microcirculation and Intracranial and Cerebral Perfusion Pressures in Severe Brain Injury - Yu. A. Churlyaev; M. Yu. Verein; D. G. Dantsiger; S. L. Kan; V. Ya. Martynenkov; Ye. V. Grigoryev (Общая реаниматология)
Objective: to evaluate the states of microcirculation, cerebral perfusion intracranial pressures in patients with isolated severe brain injury (SBI) and to determine their possible relationships. Subjects and methods. 148 studies were performed in 16 victims with SBI. According to the outcome of brain traumatic disease, the patients were divided into two groups: 1) those who had a good outcome (n=8) and 2) those who had a fatal outcome (n=8). Microcirculation was examined by skin laser Doppler flowmetry using a LAKK-01 capillary blood flow laser analyzer (LAZMA Research-and-Production Association, Russian Federation). All the victims underwent surgical interventions to remove epi-, subdural, and intracerebral hematomas. A Codman subdural/intraparenchymatous intracranial pressure (ICD) sensor (Johnson & Johnson, United Kingdom) was intraoperatively inserted in the victims. Cerebral perfusion pressure (CPP) was calculated using the generally accepted formula: CPP = MBP (mean blood pressure) — ICD. ICD, CPP, and microcirculation were studied on postoperative days 1, 3, 5, and 7. Their values were recorded simultaneously. Ninety and 58 studies were conducted in the group of patients with good and fatal outcomes, respectively. Results. No correlation between the changes in MBP, ICD, and microcirculatory parameters suggested that the value of ICD was determined by the nature of brain damage and it was the leading and determining indicator in the diagnosis and treatment of secondary cerebral lesions. The amplitude of low-frequency fluctuations directly correlated with ICD, which indicated that they might be used to evaluate cerebral perfusion and impaired cerebral circulation indirectly in victims with severe brain injury. Conclusion. The laser Doppler flowmetric technique makes it possible not only to qualitatively, but also quantitatively determine changes in the tissue blood flow system in severe brain injury. With this technique, both the local and central mechanisms which are responsible for changes in tissue blood flow autoregulation suffer, with a preponderance of the latter mechanisms. Key words: microcirculation, intracranial pressure, cerebral perfusion pressure, severe brain injury.